The Effect of Socialization, Reduction of UMKM PPH Rates and Tax Knowledge on the Implementation of Tax Regulation Harmonization Laws on Increasing Franchise UMKM Tax Compliance. - Barnomo, Maria; Hidayah, Nurul (International Journal Labs, 2025)
Tax compliance of MSMEs plays an important role in increasing state revenues, but still faces obstacles such as limited understanding and ever-changing policies. Tax socialization, reduction in Income Tax (PPh) rates for MSMEs, and tax awareness related to MSME compliance with tax regulations are the focus of this study. A total of one hundred and thirty Ayam Gepuk Pak Gembus franchisees in Jabodetabek were the subjects of the study. The calculation used the Slovin formula with a margin of error of 5% to select a sample of 171 partners using a basic random sampling approach. Data analysis used SmartPLS software and Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results of the study showed that tax awareness did not have a significant effect on compliance, but tax socialization and rate reductions had a significant effect. This indicates that simpler policies and effective socialization have a greater influence on compliance than the level of taxpayer knowledge. Implications for the government in designing strategies to improve MSME tax compliance through intensive socialization and more accessible tax policies. This suggests that simplifying tax policies and improving socialization efforts are more effective than merely increasing taxpayer knowledge. The results offer insights for policymakers to refine strategies that encourage MSME tax compliance through accessible regulations and targeted outreach.